PERCEPTION OF AGRICULTURAL EXTENSION WORKERS IN USING WEB TOOLS FOR DISSEMINATING INFORMATION IN SOUTH WEST NIGERIA - Daodu, T.O.; Henshaw, E.E.; Okoro, N.O.; Ologunagba, O.; Ajiboye, I.O.; Adara, C.T.; Uyamasi, I.M. (Nigerian Journal of Agriculture and Agricultural Technology, 2025)
The examined the perception of agricultural extension workers in using web tools for the disseminating information in southwest Nigeria. The study therefore tried to describe the socioeconomic characteristics of Agricultural extension workers, their usage of web tools in accessing agricultural information and Perception of the usage of web tools in disseminating agricultural information. A multi-stage sampling technique was used in selecting two hundred and forty-five (245) Agricultural extension workers. Primary data were collected using structured questionnaire and analyzed using descriptive analysis. Result of analysis showed that 69.5% of the extension workers were male, a high percentage (93.4%) of them were married, having their mean age as 47 years, with more than 16 years of educational qualification and work experience while their annual income was approximately N1,432,280.00. The findings further found out that the Agricultural extension workers had positive perception towards web tools usage, with all perception statements having mean values greater than 2.5. Similarly, facebook (Mean = 2.17) ranked 1st, Google plus (Mean = 2.11) ranked 2nd and WhatsApp (Mean = 2.03) ranked 3rd with a mean greater than the set threshold of greater than 2.00 were the only web tools that had high usage among agricultural extension workers in the study area. The finding concludes that the extension workers have a positive perception towards the use of web tools in disseminating agricultural information. The study therefore recommends that web tools should be designed in a user-friendly manner by key players in ICT while also training the farmers in needed areas by extension agents.